Analisis Teknik Serta Kelayakan Ekonomi Pada Perancangan Pembangkit Listrik Tenaga Surya Sistem Hybrid - Jaka Windarta; Bambang Winardi; Denis Denis; Imam Arifan Nurdani (P3M Politeknik Negeri Cilacap, 2022)
National electrical energy needs are increasing every year. This is accompanied by an increasingly massive use of fossil energy as a power plant. The government is targeting a share of new and renewable energy (EBT) of at least 23% by 2025. As a tropical country, Indonesia has a large potential for new and renewable energy, which mostly consists of solar energy with an average daily radiation of 4.8 kWh/m2/day. The design of a solar power plant (PLTS) at SMA Negeri 3 Surakarta is an effort to utilize NRE and can be used as a model for environmentally friendly schools for similar public institutions and the general public. This PLTS uses a hybrid system with a generating capacity of 1230 Wp, SCC 60A, 24 V 200 Ah battery and a 2400 W hybrid inverter. Using analysis methods with PVSyst and RetScreen simulations, this PLTS generates electricity of 1,653.2 kWh/year. With an initial investment of IDR 25,186,000, the net present value is IDR 1,210,272 and the payback period is 24 years.